About archaic words in modern Azerbaijani language (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article briefly analyzes the source, the ways of creating archaisms and their transition to passive vocabulary of the language. Due to modern dictionaries etymology of archaic words is investigated. These units are used in a certain historical period. This article also focuses on historicity, areas  of using archaic words, peculiarities of using archaic words in ancient sources language wordstock and literature works, language word stock.
Keywords: archaism; language wordstock; passive fund; modern Azerbaijan language